Terapi Akupreseur Menggunakan Aromaterapi Essensial Oil terhadap Intensitas Nyeri Haid - Neny Yuli Susanti (Universitas Malahayati Lampung, 2023)
ABSTRACT The most common menstrual problem, dysmenorrhea, is often reported by teens as an unpleasant feeling. This pain has extremely specific features since it occurs frequently and consistently along with menstruation. Pharmacological therapy has been employed more often than phytopharmaceuticals like acupressure and aromatherapy in the treatment of dysmenorrhea so far. The goal of this research was to find out whether treating teenage dysmenorrhea with a combination of acupressure and essential oil aromatherapy is effective. The quantitative analysis in this study is based on a pre- and post-test quasi-experimental design. This methodology is employed to meet the study's goals, which include determining how acupressure treatment affects the severity of menstruation discomfort (dysmenorrhoea). Young ladies with modest menstruation discomfort made up the study's population. Purposive sampling was used to choose the sample, which resulted in a final sample of 52 respondents (26 intervention groups and 26 control groups) based on the study criteria. This study was carried out at Situbondo Regency's Salafiyah Syafiiyah Islamic Boarding School. March and April of 2023 were used for the research. Research instruments included pain scale observation sheets. The statistical test that was employed had a significance level of 0.05, and it was the Wilcoxon Signed Ranks Test. Conclusion Acupressure with aromatherapy has an impact on young women's dysmenorrhea. It is advised that medical professionals, particularly midwives, promote young women's health by teaching them about acupressure using essential oils in collaboration with Islamic boarding schools as a pain-relieving option. Keywords: Acupressure, Aromatherapy, Dysmenorrhea ABSTRAK Remaja sering melaporkan mengalami dismenore, yang merupakan jenis masalah menstruasi yang paling umum. Nyeri ini memiliki ciri yang sangat spesifik karena sering terjadi dan menyertai menstruasi. Terapi farmakologi, daripada fitofarmaka seperti akupresur dan aromaterapi, sekarang lebih disukai untuk pengobatan dismenore. Tujuan penelitian ini adalah untuk mengetahui apakah akupresur dan aromaterapi menggunakan minyak esensial dapat membantu mengurangi gejala dismenore remaja. Kedua kelompok studi menjalani pra-dan pasca-pengujian sebagai bagian dari metodologi kuasi-eksperimental studi kuantitatif ini. Metodologi ini digunakan untuk memenuhi tujuan penelitian, termasuk menentukan bagaimana pengobatan akupresur mempengaruhi keparahan ketidaknyamanan menstruasi (dismenorea). Wanita muda dengan ketidaknyamanan menstruasi sedang menjadi populasi penelitian. Sampel termasuk 60 peserta (30 pada kelompok intervensi dan 30 pada kelompok kontrol), yang dipilih dengan menggunakan metode pemilihan tujuan. Penelitian ini dilakukan di Kabupaten Situbondo di Pondok Pesantren Salafiyah Syafiiyah. Penelitian dilakukan selama bulan Maret dan April 2023. Lembar observasi untuk skala nyeri berfungsi sebagai alat penelitian. Wilcoxon Signed Ranks Test dengan ambang signifikansi 0,05 adalah uji statistik yang digunakan. Kesimpulan Akupresur dengan aromaterapi berdampak pada dismenore remaja putri. Disarankan agar tenaga medis, khususnya bidan, mempromosikan kesehatan remaja putri dengan mengajarkan mereka tentang akupresur menggunakan minyak esensial bekerja sama dengan pesantren sebagai pilihan pereda nyeri. Kata Kunci: Akupresur, Aromaterapi, Dismenore